Upper- vs. Lower-Body Exercise Performance in Female and Male Cross-Country Skiers - Hansen, Linda Marie; Sandbakk, Øyvind; Ettema, Gertjan; Baumgart, Julia Kathrin (Frontiers in Sports and Active Living, 2021)
PURPOSE: To investigate the interaction between exercise modality (i.e., upper- and lower-body exercise) and sex in physiological responses and power output (PO) across the entire intensity spectrum (i.e., from low to maximal intensity). METHODS: 10 male and 10 female cross-country (XC) skiers performed a stepwise incremental test to exhaustion consisting of 5-min stages with increasing workload in upper-body poling (UP) and running (RUN) on 2 separate days. Mixed measures ANOVA were performed to investigate interactions between exercise modalities (i.e., UP and RUN) and sex in physiological responses and PO across the entire exercise intensity spectrum. RESULTS: The difference between UP and RUN (∆UP-RUN), was not different in female compared to male XC skiers for peak oxygen uptake (18±6 vs 18±6mL·kg-1·min-1, p=0.843) and peak PO (84±18 vs 91±22W, p=0.207). At most given submaximal blood lactate and rating of perceived exertion, ∆UP-RUN was larger in male compared to female skiers for oxygen uptake and PO, but these differences disappeared when responses were expressed as % of the modality-specific peak. CONCLUSION: Modality-differences (i.e., ∆UP-RUN) in peak physiological responses and PO did not differ between female and male XC skiers. This indicates that increased focus on upper-body strength and endurance training in female skiers in recent years may have closed the gap between upper- and lower-body endurance capacity compared to male XC skiers. In addition, no sex-related considerations need to be taken when using relative physiological responses for intensity regulation within a specific exercise modality.